Production of functionally graded SiC/Al-Cu-Mg composite by centrifugal casting - Savas, Omer; Kayikci, Ramazan; Ficici, Ferit; Colak, Murat; Deniz, Gurhan; Varol, Faruk (WALTER DE GRUYTER GMBH, 2016)
This study is aimed at investigating the production and wear properties of a functionally graded (FG) silicon carbide (SiC)-reinforced composite material, which was produced by stir casting followed by centrifugal casting. SiC powder (5 wt.%) was added into liquid aluminum at 750 degrees C via stir casting, at which temperature a centrifugal force was applied to the mixture to drive the SiC particles toward the outer region of the mold. The results showed that two distinct regions formed in the cast samples after the centrifugation process. The outer region showed approximately 25% SiC particles resulting in almost SiC particle-free area in the internal region of the FG SiC-reinforced composite material. The test results showed that higher hardness and higher wear resistance could be obtained at the SiC-rich periphery of the cast FG composite material.
Keywords: aluminum matrix composites; centrifugal casting; functionally graded composites; SiC; METAL-MATRIX COMPOSITES; SLIDING WEAR; MICROSTRUCTURE; Materials Science